1414. Inoculum Effect of Piperacillin/Tazobactam Concentration on Emergence of Resistance in Klebsiella aerogenes. (26th November 2018) - Custodio, Marco; Anderson, Beverly; Sanchez, Daniel; Ryan, Keenan; Walraven, Carla; Mercier, Renee-Claude
Abstract: Background: Piperacillin/tazobactam (PTZ) is a carbapenem-sparing option for AmpC-repressed organisms. Current strategies of dosing PTZ focus on prolonging f T > minimum inhibitory concentration (MIC), lowering C:MIC ratios. The objective of this study was to determine the effect of physiologic PTZ concentration on the emergence of resistance among clinical isolates of Klebsiella aerogenes (KA). Methods: Fifteen clinical KA from respiratory cultures had MICs determined by broth microdilution for PTZ and Etest for ceftriaxone (CRO) and cefepime (FEP). The presence of resistant mutants was determined using Muller–Hinton agar with increasing concentrations of CRO and PTZ. Five isolates with the highest selected MIC underwent time-kill (TK) studies with PTZ compared with CRO and FEP at high inoculum (HI) (7.0 log10 CFU/mL) and low inoculum (LI) (5.0 log10 CFU/mL). Concentrations used in TK studies simulated lung epithelial lining fluid for free peak of a prolonged infusion of PTZ (20 µg/mL; PTZ20) and the average AUC0–24 (10 µg/mL; PTZ10), continuous infusion FEP (8 µg/mL), and the average AUC0–24 concentration of CRO (6 µg/mL). Results: MICs for PTZ, FEP and CRO ranged from 2 to 8, 0.47 and 0.094 to 0.125 µg/mL, respectively. Mutant selection for both PTZ and CRO occurred for five isolates. In TK studies at HI, FEP was the only agent to demonstrate bactericidal activity with reduction of 5.0 ± 0.7 log10 CFU/mL. Reductions for PTZ20 and PTZ10 were 0.21 ± 0.18 and 0.05 ± 0.16 log10 CFU/mL, respectively. CRO demonstrated regrowth of 0.5 ± 0.3 log10 CFU/mL. Interestingly, the susceptibility before and after TK did not differ for the PTZ groups, whereas all CRO-exposed isolates had become resistant. At LI, PTZ20 and PTZ10 had improved activity with reductions of 3.0 ± 0.4 and 2.8 ± 0.5 log10 CFU/mL, respectively. CRO was also more active at LI but with regrowth for 2/5 isolates. Conclusion: In studies simulating conditions of pneumonia, PTZ demonstrated significant inoculum-dependent killing regardless of baseline MIC. CRO demonstrated selection for resistance at HI and variably at LI. FEP was the only antimicrobial associated with bactericidal activity at HI. Resistance to PTZ was seen on agar plates although not in TK studies. Dosing strategies to optimize cidality are warranted. Disclosures: All authors: No reported disclosures.